Thinking biblically about Islam : Genesis, transfiguration, transformation - Glaser, Ida (Langham Global Library, 2016)
In this careful double exposition of the Bible and Islam, Ida Glaser and Hannah Kay emphasize godly attitudes, loving action and a deep appreciation of God's grace and goodness as essential traits of any Christian. The authors walk the reader through two underlying frameworks necessary to think biblically about Islam. The first is to understand the dynamic of religion in people's lives through Genesis 4-11's account of the world after 'the fall', and hence to understand Bible stories within the religious contexts in which they occurred. The second is at the heart of the book - the idea that Islam inverts the exaltation of Christ above the prophets in the narrative of the transfiguration in Luke 9 and 10. Examining the themes of the land, zeal, law and the cross in these chapters of Luke's Gospel and the Old Testament stories of Moses and Elijah, we are led to better understand the Bible, Islam and God's heart towards Muslims.